Economic evaluations of scaling up strategies of evidence-based health interventions: a systematic review - Adissa Bankolé; Blanchard Conombo; France Légaré; Maude Laberge (BMC Health Services Research)
Abstract Background Scaling seeks to extend the benefits of evidence-based interventions (EBIs) to larger populations, and often with the hope of achieving economies of scale. However, little is known about scaling costs. Our goal was to find scaling studies that focused on economic evaluations of scaling, their characteristics and the methods they applied. Methods We performed a systematic review informed by the Joanna Briggs Institute and PRISMA reporting guidelines. We included all studies that conducted a full or partial economic evaluation of scaling an EBI in healthcare, applicable to any individual or organization in any country and setting. We included all study designs and imposed no restrictions on language. We conducted searches in Medline, Web of Science, Embase, Cochrane Library Database, PEDE, EconLIT, INHATA from their inception until November 12, 2024, including grey literature. Pairs of independent reviewers identified eligible studies and extracted data on study characteristics, scaling strategies, characteristics of economic evaluations and methods used. The methodological quality of included studies was evaluated using the British Medical Journal Checklist. Results were summarized using narrative synthesis. Results Of 8,936 unique citations, thirteen studies meet our inclusion criteria: ten cost-effectiveness and three cost-analysis studies. Studies were performed in lower- or middle-income countries (LMIC) as well as in high-income countries and covered EBIs for infectious diseases, mental health, and colorectal cancer. All reported direct costs (e.g., health professional training costs) and indirect costs (e.g., capital costs) associated with scaling strategies. Four studies were of high quality, eight of moderate quality and one of poor quality. Conclusion With the increased interest in scaling EBIs in health, there is an urgent need for more evaluations of costs associated with scaling, both in LMIC and in high-income countries, and a need for rigour in how these evaluations are performed.